Sea algae from Isla Verde, Veracruz, Mexico - Mateo-Cid, Luz Elena; Mendoza-Gonzalez, A. Catalina; Galicia Garcia, Citlalli (Instituto de Ecología, A.C., 1996)
A study on benthic marine algae from Isla Verde, Veracruz in the waters of the Gulf of Mexico revealed the existence of 5 species of Cyanophyceae, 37 species of Rhodophyceae, 6 of Phaeophyceae, 8 species of Bacillariophyceae and 24 of Chlorophyceae. The study includes information on seasonality, reproductive stage, tidal level, wave exposure, substrate and epiphytism. The species composition found in Isla Verde is of tropical affinity and representative of the algal flora associated with coral reefs as was expected. Species diversity in relation to substrate, ligth and temperature is discussed.